Pengaruh Gaya Komunikasi Pengasuh terhadap Kemampuan Sosial Anak di Tempat Penitipan Anak Al-Wathaniyah - Sulastya Ningsih; Nurain Yusuf; Fitra Mulyani Abdullah; Riyanti Latama; Nurul Fazrun Dadu (Khirani: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to analyze the influence of caregivers’ communication styles on children’s social skills at daycare centers in Al-Wathaniyah. The research employed a quantitative correlational approach, involving 50 children aged 3–6 years and their caregivers as research participants. Data were collected through questionnaires and observations measuring caregivers’ communication styles, including verbal, non-verbal, empathy, and responsiveness, as well as children’s social skills, which consist of interaction, sharing, cooperation, and emotional expression. Data analysis was conducted using descriptive statistics and Pearson correlation. The results showed that caregivers’ communication styles were categorized as high, and children’s social skills were also high. A significant positive relationship was found between caregivers’ communication styles and children’s social skills, with a correlation value of r = 0.72 and p < 0.05. This study confirms that caregivers who employ warm, empathetic, and responsive communication can enhance children’s social skills optimally. The findings are relevant for daycare managers, caregivers, and parents to support children’s social development through effective communication.